2023
DOI: 10.3390/diagnostics13111924
|View full text |Cite
|
Sign up to set email alerts
|

Automatic and Early Detection of Parkinson’s Disease by Analyzing Acoustic Signals Using Classification Algorithms Based on Recursive Feature Elimination Method

Abstract: Parkinson’s disease (PD) is a neurodegenerative condition generated by the dysfunction of brain cells and their 60–80% inability to produce dopamine, an organic chemical responsible for controlling a person’s movement. This condition causes PD symptoms to appear. Diagnosis involves many physical and psychological tests and specialist examinations of the patient’s nervous system, which causes several issues. The methodology method of early diagnosis of PD is based on analysing voice disorders. This method extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Applying t-SNE to select the most important features and reduce the dimensionality of facial features extracted by VGG16, ResNet101, and MobileNet models for autism analysis brings several significant advantages: While deep learning models like VGG16, ResNet101, and MobileNet are powerful at extracting meaningful features from images, the features they produce often be high-dimensional and redundant. High dimensionality increases computation time and even introduces noise or irrelevant information into the analysis [ 38 ]. Applying t-SNE effectively reduces the dimensionality of the extracted features while preserving the most important information.…”
Section: Methodsmentioning
confidence: 99%
“…Applying t-SNE to select the most important features and reduce the dimensionality of facial features extracted by VGG16, ResNet101, and MobileNet models for autism analysis brings several significant advantages: While deep learning models like VGG16, ResNet101, and MobileNet are powerful at extracting meaningful features from images, the features they produce often be high-dimensional and redundant. High dimensionality increases computation time and even introduces noise or irrelevant information into the analysis [ 38 ]. Applying t-SNE effectively reduces the dimensionality of the extracted features while preserving the most important information.…”
Section: Methodsmentioning
confidence: 99%
“…Parkinson's, a disease caused by a lack of dopamine, is often present for several years before the diagnosis is made. Machine learning applied to voice recordings can be used to detect Parkinson's disease automatically and early, allowing earlier treatment and better quality of life for sufferers ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proposed biomarkers include clinical, imaging, biofluidic-base, and inflammation-related biomarkers for preclinical, prodromal, and clinical stages [ 9 , 10 ]. Some of the proposed tools and methods for the early detection of PD are based on analysing voice disorders [ 11 , 12 ], handwriting [ 13 ], olfactory testing [ 14 ], and accelerometery data [ 15 ]. Other proposed solutions based on the use of Artificial Intelligence include convolutional neural networks for eye tracking and facial expression analysis [ 16 ], Machine Learning-assisted speech analysis [ 17 ], and deep learning models for various modalities such as brain analysis and motion symptoms [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are currently no means to identify prodromal PD with 100% certainty [ 19 ], neither standardized international criteria supporting PD diagnosis at a preclinical stage [ 10 ] nor confirmed biomarkers to provide early detection of PD efficiently [ 11 , 20 ]. On the other hand, an increasing number of studies have revealed that a combination of biomarkers can improve the diagnostic accuracy of individual biomarkers [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%